The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.heliyon.2021.e06190
|View full text |Cite
|
Sign up to set email alerts
|

New methods of posturographic data analysis may improve the diagnostic value of static posturography in multiple sclerosis

Abstract: Background Early and accurate diagnosis of multiple sclerosis (MS) is crucial for its effective treatment. In MS diagnostic, neuronal networks that control posture and movement are of particular importance, which performance can be assessed using static posturography. Unfortunately, most of the commercially available posturographic platforms are not equipped with the appropriate procedures. Methods To solve this problem, the postural sway trajectories have been recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Plantar pressure refers to the pressure exerted on the sole of the foot during activities such as standing and walking. Studies have indicated that individuals with ACL rupture may exhibit abnormal plantar pressure distribution, which can impact their walking and running mechanics [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plantar pressure refers to the pressure exerted on the sole of the foot during activities such as standing and walking. Studies have indicated that individuals with ACL rupture may exhibit abnormal plantar pressure distribution, which can impact their walking and running mechanics [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Knee instability can lead to impaired balance, increasing the risk of falls and other injuries. Additionally, alterations in plantar pressure distribution may affect an individual's balance, as plantar pressure plays a crucial role in maintaining balance during gait and other activities [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…MS has a wide range of focal neurological symptoms associated with psychological and cognitive manifestations. 8 , 9 Its psychological and social burden on the patients is considerable. Cognitive impairment is one of its most common symptoms.…”
Section: Introductionmentioning
confidence: 99%